2013
DOI: 10.1016/j.socscimed.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic density and area deprivation: Neighbourhood effects on Māori health and racial discrimination in Aotearoa/New Zealand

Abstract: Some studies suggest that ethnic minority people are healthier when they live in areas with a higher concentration of people from their own ethnic group, a so-called ethnic density effect. To date, no studies have examined the ethnic density effect among indigenous peoples, for whom connections to land, patterns of settlement, and drivers of residential location may differ from ethnic minority populations.The present study analysed the Māori sample from the 2006/07 New Zealand Health Survey to examine the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 27 publications
3
83
1
Order By: Relevance
“…Although a study by Gilbert et al (2013) established a decline in infant mortality across neighbourhood income quintiles over time in Canada, the study indicates the need for infant health promotion policies among the vulnerable populations. A study by Becares et al (2013) established association between area deprivation and poor health outcomes, and concludes that addressing neighbourhood poverty and area deprivation is essential to improving health outcomes of individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Although a study by Gilbert et al (2013) established a decline in infant mortality across neighbourhood income quintiles over time in Canada, the study indicates the need for infant health promotion policies among the vulnerable populations. A study by Becares et al (2013) established association between area deprivation and poor health outcomes, and concludes that addressing neighbourhood poverty and area deprivation is essential to improving health outcomes of individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Community connection’s effect in encouraging mammograms is localized to a mostly Black and Hispanic area. This could be a reflection of a phenomenon known as ‘ethnic density.’ Ethnic density a process identified in several countries wherein minorities residing in mostly minority communities, such as places racially segregated, gain protective health effects from the close connections and reduced discrimination enjoyed in these places [38, 60, 61]. Indeed, it would support Dean’s et al [14] theory that Black women are more likely to pursue mammograms in their local context based on the presence of local community connection.…”
Section: Resultsmentioning
confidence: 99%
“…It may be that despite significant disadvantage, Indigenous culture actually forms a protective factor against psychiatric disorders: research has found that for Maori people, connection to culture is linked to greater resilience (Muriwai et al, 2015) and subjective well-being (Houkamau and Sibley, 2011). Further, research has found that living in areas of higher ethnic density is linked to better health outcomes, such as lower diagnosed psychiatric disorders and higher self-reported health in Maori people (despite deprivation in these regions; Bécares et al, 2013) and less psychological distress in Indigenous Australian people (Cunningham and Paradies, 2012). Interestingly, Bécares et al's study found that psychological distress was highest in areas of higher deprivation-these areas also happened to have higher Maori density, and lower rates of psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%